P-136 Hospice ultrasound availability enabling out of hospital paracentesis during the first COVID lockdown. A review of paracentesis achieved and their sonographic appearances. (19th November 2022) - Eastman, Jo; Gray, Anna; Midgley, Corinna
Abstract : Background: Like many other hospitals in the UK, the NHS trust local to Saint Francis Hospice (SFH) became overwhelmed with COVID patients during the first lockdown (April to June 2020). The Trust struggled to access a hospital bed for people with advanced disease requiring paracentesis, and getting a permanent drain was difficult. The use of ultrasound in hospices has grown in recent years; its usefulness in hospice paracentesis is well documented. Knowing that SFH had access to ultrasound gave oncology and cardiac colleagues' confidence to offer the hospice as an alternative. Aims: To identify by retrospective notes review whether the first lockdown affected frequency of paracentesis procedures carried out by the hospice, to identify any obstacles to smooth admission/procedure, and to identify outcomes. Methods: Retrospective review of hospice notes, search term 'paracentesis', 'ascites'. Results: Eighteen drainages were carried out on 8 patients during the 9 month period 08/10/2019 – 30/06/2020. Five had advanced cancer and three had heart failure. 11 were carried out pre-lockdown and 7 during it, a rate increase during lockdown. No permanent drains were achieved during lockdown. 16/18 were planned admissions for paracentesis (2 were crisis admissions for other reasons). All had ultrasounds pre- procedure. Average wait from referral to admission 5.9 days; Average time drain in situ 53 hours; Average volume drained 9.4L. Positive feedback from patients, and no adverse events attributable to the procedure. The audit identified need for adjustment of the admission process to avoid delays from blood tests awaited or sonographer unavailability. Conclusion: Availability of ultrasound allowed safe paracentesis in the hospice and contributed to timely patient care/protection of hospital beds. This poster will provide an overview of typical sonographic appearances of ascites and highlight scenarios that may influence the suitability of drainage.